Creep behavior of thin-walled circular steel tubular columns filled with demolished concrete lumps and fresh concrete. (30th October 2018) - Wu, Bo; Lin, Lang; Zhao, Junxian; Yan, Hua
Highlights: Creep tests conducted on 4 thin-walled CFST columns with compound concrete. Creep tests conducted on 6 cylinders with compound concrete. Modified Counto model proposed to predict creep of compound concrete in cylinders and CFST columns. Basic creep of the specimens are well predicted by the proposed model. Abstract: Structural members containing large-scale (60–300 mm) demolished concrete lumps (DCLs), proposed previously by the authors, are new approaches for recycling demolished concrete to reduce the consumption of cement and the cost of labor during manufacturing of conventional small-scale recycled aggregates (≤31.5 mm) from existing buildings. The authors' previous researches focused on the short-term mechanical behaviors of thin-walled circular steel tubular columns with compound concrete (referred to as compound CFST columns). In this paper, study is extended to experimental and theoretical studies on the long-term creep behaviors of compound CFST columns (4 specimens) and their cylindrical core counterparts (6 specimens), in which the effect of DCL replacement ratio and axial compression ratio on their creep behaviors were considered. Test results show that: (1) the basic creep of cylindrical compound concrete specimens was greater than those of the cylindrical FC or demolished concrete specimens, but increased with the rise of DCL replacement ratio; (2) the compound CFST specimens had nearly identical creep behaviors with the CFST specimens with FC only; (3) the experimental elastic modulus and basic creep were over- and under-estimated, respectively, by the Counto model, a two-phase composite model that regards the DCL and FC as the aggregate and matrix phases, respectively. A modified Counto model that considers the effect of micro-cracks within the DCLs and the DCL replacement ratio is proposed to predict the basic creep of the compound concrete with and without circular tube. Effectiveness of this approach is validated by experiments finally.